Design and evaluation of a passive compliance control method of an offshore wind turbine blade grinding robot - Liu, Xinrong (Strojniški vestnik, 2025)
Robots that repair offshore wind turbine blades are susceptible to interference from different factors such as external wind, which can lead to damage to the blades by the robot during the grinding process. Therefore, the robot needs to keep the grinding contact force constant in the complex operating environment. In this study, a constant force control device that is based on a pneumatic system is designed to address this problem, and a controller that is based on an improved Active Disturbance Rejection Control (ADRC) algorithm was proposed to control this device. Based on the analysis of the mechanism of the constant force control device and according to the relative order of the system, a second-order ADRC is designed. The controller utilizes a tracking differentiator (TD) to filter the input signal, an extended state observer (ESO) to estimate the total perturbation in the system, and a nonlinear state error feedback control law (NLSEF) for compensation. In order to solve the problems of electric proportional valve dead-zone characteristics, unknown interference during high altitude operation, tilt angle changes during grinding, dead-zone compensation, and gravity compensation algorithms were incorporated into the controller. Finally, the experimental platform is built to carry out experiments under various working conditions. The experimental results show that the controller improves the system regulation time by 59%, with an overshoot close to zero, when compared with the traditional proportional-integral-derivative (PID) algorithm. Also, both the absolute value of the maximum error and the mean square value of the error have been reduced to a large extent. As a result, the controller has a better force control accuracy and dynamic tracking performance, strong interference rejection capability and adaptability, and provides a theoretical basis for practical engineering applications.
Keywords: dead-zone compensation; gravitacijska kompenzacija; gravity compensation; improved active disturbance rejection control; izboljšani aktivni nadzor zavrnitve motenj; kompenzacija mrtvega območja; lopatica vetrne turbine na morju; offshore wind turbine blade; pneumatic loading system; pnevmatski obremenilni sistem